2011
DOI: 10.1002/hipo.20834
|View full text |Cite
|
Sign up to set email alerts
|

Functional phenotyping of successful aging in long‐term memory: Preserved performance in the absence of neural compensation

Abstract: We investigated whether preservation of encoding-related brain activity patterns in older age reflects successful aging in long-term memory. Using a statistical matching technique, we identified groups of healthy older adults with different degrees of Functional Activity Deviation during Encoding (FADE) from young adults in a memory network comprising hippocampal, temporal, occipital, and retrosplenial regions. High FADE scores were associated with impairment in recollection, abnormal activity in the default m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
183
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(206 citation statements)
references
References 63 publications
17
183
1
Order By: Relevance
“…Furthermore, a third set of imaging data suggested that young and elderly participants with high performance on cognitive tasks recruited a similar network of brain regions [30][31][32]91]. These findings drew attention to brain maintenance hypothesis [15].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Furthermore, a third set of imaging data suggested that young and elderly participants with high performance on cognitive tasks recruited a similar network of brain regions [30][31][32]91]. These findings drew attention to brain maintenance hypothesis [15].…”
Section: Discussionmentioning
confidence: 81%
“…Another pattern of imaging findings described similar networks of brain regions recruited by younger and high-performing older adults [15,[30][31][32] and leaded to discuss that the lack of functional changes could constitute a determinant of successful memory aging.…”
Section: Introductionmentioning
confidence: 94%
“…In young adults, DN regions maintain strong functional interconnections during tasks requiring self-reference or theory of mind 101,102 , and also during the resting state 103,104 . Several studies have found that the reduction of DN activity during externally-driven cognitive tasks is less pronounced in old adults, relative to young adults 58,[105][106][107][108][109][110][111][112] . Functional connectivity of the DN also is reduced with age during working memory tasks 113 and during periods of rest 105,[114][115][116] .…”
Section: Box 1 Measuring Activity In Brain Networkmentioning
confidence: 99%
“…Several studies have found that the reduction of DN activity during externally-driven cognitive tasks is less pronounced in older adults, relative to younger adults (Andrews-Hanna et al, 2007;Damoiseaux et al, 2008;Duzel, Schutze, Yonelinas, & Heinze, 2011;Esposito et al, 2008;Grady et al, 2010;Grady, Springer, Hongwanishkul, McIntosh, & Winocur, 2006;Lustig et al, 2003;Miller et al, 2008;Persson, Lustig, Nelson, & Reuter-Lorenz, 2007). Intrinsic functional connectivity within the DN during periods of rest also is reduced in older relative to younger adults (Andrews-Hanna, et al, 2007;Hedden et al, 2009;Park, Polk, Hebrank, & Jenkins, 2010), and age reductions during memory tasks also have been noted (Sambataro et al, 2010;Wang, Li, Metzak, He, & Woodward, 2010).…”
Section: The Default Network (Dn)mentioning
confidence: 99%